The face of another - Abe, Kōbō 1924-1993; Takemitsu, Tōru 1930-1996 (Criterion Coll., 2007)
A man disfigured in an industrial accident, who receives a face transplant created from a stranger, finds himself becoming increasingly isolated from those around him.
Aspect ratio 1.33:1. - New, restored high-definition digital transfer
Orig.: Japan 1966
Enth. video essay on the film by critic and festival programmer James Quandt
Keywords: Disfigured persons -- Drama; Feature films; Feature films -- Japanese language; Identity (Psychology) -- Drama; Interpersonal relations -- Drama; Science fiction films